2015
DOI: 10.1371/journal.pone.0118241
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Treatment of Severe Exacerbations of Chronic Obstructive Pulmonary Disease with Procalcitonin: A Randomized Noninferiority Trial

Abstract: BackgroundThe duration of antibiotic treatment of exacerbations of COPD (ECOPD) is controversial. Serum procalcitonin (PCT) is a biomarker of bacterial infection used to identify the cause of ECOPD.Methods and FindingsWe investigated whether a PCT-guided plan would allow a shorter duration of antibiotic treatment in patients with severe ECOPD. For this multicenter, randomized, non-inferiority trial, we enrolled 184 patients hospitalized with ECOPD from 18 hospitals in Italy. Patients were assigned to receive a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
48
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(49 citation statements)
references
References 32 publications
0
48
0
1
Order By: Relevance
“…Nseir et al [44] reported that PCT >0.5 ng/ml with a positive Gram stain for endotracheal aspirate was associated with bacterial exacerbations. In a multicenter randomized controlled study from Italy, the authors compared 10 days of antibiotic treatment with discontinuation of antibiotics within 3 days plus PCT guidance in patients hospitalized for COPDE [20]. It was found that discontinuing antibiotics on day 3 with PCT <0.25 ng/ml was a safe method, and there was no difference between the groups for outcomes such as exacerbation rate, hospital/ICU admission functional status decline, and mortality within a 6-month period.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nseir et al [44] reported that PCT >0.5 ng/ml with a positive Gram stain for endotracheal aspirate was associated with bacterial exacerbations. In a multicenter randomized controlled study from Italy, the authors compared 10 days of antibiotic treatment with discontinuation of antibiotics within 3 days plus PCT guidance in patients hospitalized for COPDE [20]. It was found that discontinuing antibiotics on day 3 with PCT <0.25 ng/ml was a safe method, and there was no difference between the groups for outcomes such as exacerbation rate, hospital/ICU admission functional status decline, and mortality within a 6-month period.…”
Section: Discussionmentioning
confidence: 99%
“…First, it was performed on severe COPDE patients who required ICU admission. Most PCT studies in the literature evaluated prognosis mostly in mild-to-moderate COPDE either in the emergency room or the hospital ward [17,19,20]. Second, the study included patients with severe COPD, mostly GOLD stages III and IV.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors did not report any difference in the length of stay in ICU between groups, as well as no difference in mortality and adverse events [7]. In a recent study that we conducted in patients admitted to hospital for severe exacerbations of COPD associated with clinical signs of bacterial infections (increased and purulent sputum and/or respiratory failure), the PCT-guided reduction of duration of antibiotic treatment from 3 to 10 days was not associated with increased risk of exacerbations in the following 6 months [8].…”
mentioning
confidence: 86%
“…Recently, the clearance of serum PCT has been shown to be useful in driving the duration of antibiotic therapy in patients affected by pneumonia [1] or COPD exacerbation (COPDE) [2,3] , but these latter findings require further confirmation. Finally, the role of PCT in diagnosis and prognosis among critically infectious patients is still controversial.…”
mentioning
confidence: 99%